The Effect of a Sibling's Gender on Earnings, Education and Family Formation - Noemi Peter; Petter Lundborg; Sara Mikkelsen; Dinand Webbink (Lund University, School of Economics and Management, Department of Economics, 2018)
We examine how the gender of a sibling affects earnings, education and family formation. Identification is complicated by parental preferences: if parents prefer certain sex compositions over others, children's gender affects not only the outcomes of other children but also the existence of potential additional children. We employ two empirical strategies that both address this problem. First, we look at a sample of dizygotic (i.e. non-identical) twins. Second, we use a large sample of singletons to estimate whether first-borns are affected by the gender of their second-born sibling. We find that a same-sex sibling increases men's earnings and family formation outcomes (marriage and number of children), as compared to an opposite-sex sibling. Women with a same-sex sibling also earn more and are somewhat more likely to form a family in the singleton sample. A large part of the positive effect on men's income can be explained by competition among brothers. Women on the other hand seem to benefit from sisters because of shared labor market networks. The effects on family formation might stem from differential parental treatment for men, and from competition between sisters for women.
Keywords: J00; J13; J16; J24; 330; sibling gender; sex composition; twins; income; schooling; fertility